Photodynamic therapy in the treatment of glioma - Zavadskaya, Т.S. (Experimental Oncology, 2015)
The review presents the data on the use of photodynamic therapy (PDT) for the treatment of patients with malignant brain tumors. One and two-year survival rate and an increase in overall median survival of PDT-treated patients compared with standard treatment indicate a promising prospects for PDT in neurooncology. Кey Words: glioblastoma, photodynamic therapy, photosensitizer, chlorin e6.